The expression, as given, cannot be factorised.
(3b - 1)(a - b)
(a - 2b)(c - 3d)
(2a + 3)(b - 3c)
ac + 2ad + 2bc + 4bd = a(c + 2d) + 2b(c + 2d) = (a + 2b)(c + 2d) Now expand to confirm your answer: c(a + 2b) + 2d(a + 2b) = ac + 2bc + 2ad + 4bd ≡ ac + 2ad + 2bc + 4bd
ac-5ad-5bc+25bd a(c-5d)-5b(c-5d) (a-5b)(c-5d) FOIL First (a*c=ac) Outside (a*-5d=-5ad) Inside (-5b*c=-5bc) Last (-5b*-5d=25bd) ac-5ad-5bc+25bd
Divide the product by one of the multiplicands. The answer should be the other multiplicand.
You make a check by they're name, then go to delete.
When multiplying exponential factors the exponents are added if bases are the same. 5^3 * 5^4 = 5^7 check it out on your calculator.
you have to check it...